2021
DOI: 10.1055/s-0041-1732417
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Quaternary Neonatal Management of Posthemorrhagic Hydrocephalus

Abstract: Objective This study aimed to determine clinical care practices for infants at risk for posthemorrhagic hydrocephalus (PHH) across level IV neonatal intensive care units (NICUs). Study Design Cross-sectional survey that addressed center-specific surveillance, neurosurgical intervention, and follow-up practices within the Children's Hospitals Neonatal Consortium. Results We had a 59% (20/34 sites) response rate, with 10 sites having at least two participants. Respondents included neonato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Head circumference with or without clinical symptoms was frequently used for surveillance and often important for timing of intervention. Notably, we also found significant perceived intracentre differences in the approach to PHH management between neonatology and neurosurgical disciplines, even with a multidisciplinary standardised approach in place 29. This is a potential area for quality improvement in the CHNC network.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Head circumference with or without clinical symptoms was frequently used for surveillance and often important for timing of intervention. Notably, we also found significant perceived intracentre differences in the approach to PHH management between neonatology and neurosurgical disciplines, even with a multidisciplinary standardised approach in place 29. This is a potential area for quality improvement in the CHNC network.…”
Section: Discussionmentioning
confidence: 75%
“…In our study, we found significant variation in the per cent of infants having VAD placement, which was the most common TD in our cohort. We previously reported approaches to surgical intervention for PHH in CHNC centres 29. While specific approaches vary by centre, some themes emerged.…”
Section: Discussionmentioning
confidence: 99%